2020
DOI: 10.1177/0956462420924984
|View full text |Cite
|
Sign up to set email alerts
|

A realist systematic review of stigma reduction interventions for HIV prevention and care continuum outcomes among men who have sex with men

Abstract: While stigma associated with human immunodeficiency virus (HIV) infection among men who have sex with men (MSM) is well recognized, there remains relatively limited intervention data on effective stigma reduction strategies. This systematic review was conducted to highlight the mechanisms through which sexual and HIV stigma is reduced in relation to HIV prevention and care engagement. Search of PubMed and Scopus resulted in 11 tested interventions to include in our preliminary model constructed from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Research into stigma particularly the impact of living with epilepsy has shown that stigma can result in a perceived reduction in social value and poor quality of life [ 56 ]. Interventions to address stigma with people affected by HIV [ 57 ] and mental health conditions [ 58 ] has been widely published and emphasise the importance of social connection and education. There is little evidence to guide interventions to address stigma with plwLTNCs and is an area that needs greater research attention.…”
Section: Discussionmentioning
confidence: 99%
“…Research into stigma particularly the impact of living with epilepsy has shown that stigma can result in a perceived reduction in social value and poor quality of life [ 56 ]. Interventions to address stigma with people affected by HIV [ 57 ] and mental health conditions [ 58 ] has been widely published and emphasise the importance of social connection and education. There is little evidence to guide interventions to address stigma with plwLTNCs and is an area that needs greater research attention.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a substantial number of systematic reviews has been published that address different aspects of HIV-related stigma and discrimination. These include associations of stigma (covariates, causes or effects), 13–40 access to care, 41–66 HIV testing, 67–91 country-specific explorations of stigma or discrimination, 92–109 the role of stigma and discrimination in treatment adherence, 110–127 HIV experiences of people living with HIV or their care givers, 128–141 stigma/discrimination reduction in the community, 142–153 HIV disclosure considerations, 154–162 stigma/discrimination in healthcare, 163–170 rights and regulations, 171–177 intersectionality, 178–183 measuring stigma, 184–189 HIV prevention, 190–193 stigma reduction in low income countries, 194–197 self-stigma 7 198 199 and other, unique topics. 200 201 We build on these reviews which outline existing research and point to persistent knowledge gaps.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Stigma and discrimination are widely considered primary drivers of the disproportionate global burden of HIV on gay, bisexual, and other men who have sex with men and on transgender women 1 [1][2][3][4][5]. In 2018, UNAIDS estimated gay, bisexual, and other men who have sex with men were at 22 times greater risk of HIV acquisition than members of the general population [6].…”
Section: Introductionmentioning
confidence: 99%